2018
DOI: 10.31018/jans.v10i1.1566
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis in tossa jute (Corchorus olitorius L.) germplasm lines

Abstract: An experiment was conducted to examine the magnitude of genetic diversity and characters contributing to genetic diversity among 81 tossa jute genotypes. Cluster analysis based on Euclidean squared distances and ward's method, the genotypes were grouped into ten distinct clusters. Analysis reveals that stick weight contributes maximum to the phenotypic diversity (65.52%) followed by green weight (13.64%) and fibre yield (10.10%). Among the clusters Cluster IX recorded highest mean fibre yield (19.91g) followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 4 publications
(5 reference statements)
4
14
0
Order By: Relevance
“…In the present study, the highest intracluster distances were recorded in cluster III (10.138), indicating high variation among the genotypes in the cluster and lowest in cluster I (3.530) indicating less variation among the genotypes in this cluster. The average intercluster distances were higher than the average intracluster distances, which indicates the presence of wide genetic diversity among the genotypes of different clusters than those of the same cluster [57].…”
mentioning
confidence: 75%
“…In the present study, the highest intracluster distances were recorded in cluster III (10.138), indicating high variation among the genotypes in the cluster and lowest in cluster I (3.530) indicating less variation among the genotypes in this cluster. The average intercluster distances were higher than the average intracluster distances, which indicates the presence of wide genetic diversity among the genotypes of different clusters than those of the same cluster [57].…”
mentioning
confidence: 75%
“…However, the mean value of different clusters varied in magnitude that also implies more diversity among the genotypes for all the fifteen characters. Similar findings were also observed by Arpita and Kumar (2016), Alam (2011), Roy et al (2011), Ghosh et al (2014) and Jatothu et al (2018) while studying the genetic diversity in Corchorus spp.…”
Section: Cluster Mean Analysissupporting
confidence: 87%
“…So, more emphasis should be given on clusters I and IV to obtain stronger heterosis and broad spectrum of variability in segregatants with new recombination of desired traits. Arpita and Kumar (2016), Akter et al (2010); Roy et al (2011) and Jatothu et al (2018) also reported similar findings while studying genetic diversity in tossa jute germplasm.…”
Section: Figure 1 Four Clusters Of Twenty-one Genotypes Of Tossa Jutementioning
confidence: 60%
See 2 more Smart Citations